Impulsively-Laser Excitation and Propagation of Ultrasonic Waves through Nanomagnetic Fluid - A. R. Baev; A. I. Мitkovets; M. V. Asadchaya; A. L. Mayorov (Приборы и методы измерений)
Magnetic fluids belong to the class of nanomaterials with a high gain of light absorption, aggregative and sedimentation stability as well as controllability by external fields, which is of interest to use in the field of optoacoustics. The purpose of the work was to experimentally study the effect of the optoacoustic transformation in a magnetic fluid, depending on the concentration of magnetic colloidal particles, boundary conditions, intensity of the laser as well as to identify the possibilities of using the magnetic fluid as an element of the optoacoustic transformation in a number of applications.A brief analysis of the optoacoustic transformation mechanism in a magnetic fluid was carried out and a technique and an installation that implements the shadow measurement variant developed. A Lotis type laser was used as a source of ultrasonic pulse-laser excitation in magnetic fluids. A quartz and air were used as a material transmitting the energy of laser radiation in a magnetic fluid. Receiving of ultrasound signals was made by a piezoelectric probe at a working frequency of 5 MHz. In the measurement process, the concentration of the dispersed phase in tmagnetic fluid was varied from zero to 8 % and the energy in the impulse – from zero to 10 mJ.For the first time, it was established that: a) an amplitude of the function of the optoacoustic transformation in a magnetic fluid, depending on the concentration of the dispersed phase, has a maximum determined by the fluid physical properties and boundary conditions; b) for all samples within the measurement error, a quasilinear dependence of the specified amplitude of energy in the laser pulse in the range of 0–8 MJ has been established.A number ways of the optoacoustic effects in magnetic fluids to use in ultrasonic testing, measuring the intensity of the laser radiation had been suggested.